Are pharmacy-based minor ailment schemes a substitute for other service providers?: A systematic review - Paudyal, Vibhu (Royal College of General Practitioners, 2013)
BACKGROUND: Pharmacy-based minor ailment schemes (PMASs) have been introduced throughout the UK to reduce the burden of minor ailments on high-cost settings, including general practice and emergency departments. AIM: This study aimed to explore the effect of PMASs on patient health- and cost-related outcomes; and their impact on general practices. DESIGN AND SETTING: Community pharmacy-based systematic review. METHOD: Standard systematic review methods were used, including searches of electronic databases, and grey literature from 2001 to 2011, imposing no restrictions on language or study design. Reporting was conducted in the form recommended in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and checklist. RESULTS: Thirty-one evaluations were included from 3308 titles identified. Reconsultation rates in general practice, following an index consultation with a PMAS, ranged from 2.4% to 23.4%. The proportion of patients reporting complete resolution of symptoms after an index PMAS consultation ranged from 68% to 94%. No study included a full economic evaluation. The mean cost per PMAS consultation ranged from £1.44 to £15.90. The total number of consultations and prescribing for minor ailments at general practices often declined following the introduction of PMAS. CONCLUSION: Low reconsultation and high symptom-resolution rates suggest that minor ailments are being dealt with appropriately by PMASs. PMAS consultations are less expensive than consultations with GPs. The extent to which these schemes shift demand for management of minor ailments away from high-cost settings has not been fully determined. This evidence suggests that PMASs provide a suitable alternative to general practice consultations. Evidence from economic evaluations is needed to inform the future delivery of PMASs.